Diarrheal-associated gut dysbiosis in cancer and inflammatory bowel disease patients is exacerbated by Clostridioides difficile infection - Kulecka, Maria; Zeber-Lubecka, Natalia; Bałabas, Aneta; Czarnowski, Paweł; Bagińska, Katarzyna; Głowienka, Maria; Kluska, Anna; Piątkowska, Magdalena; Dąbrowska, Michalina; Waker, Edyta; Mikula, Michał; Ostrowski, Jerzy (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Low diversity gut dysbiosis can take different forms depending on the disease context. In this study, we used shotgun metagenomic sequencing and gas chromatography–mass spectrometry (GC-MS) to compared the metagenomic and metabolomic profiles of Clostridioides (Clostridium) difficile diarrheal cancer and inflammatory bowel disease (IBD) patients and defined the additive effect of C. difficile infection (CDI) on intestinal dysbiosis. Results The study cohort consisted of 138 case-mix cancer patients, 43 IBD patients, and 45 healthy control individuals. Thirty-three patients were also infected with C. difficile. In the control group, three well-known enterotypes were identified, while the other groups presented with an additional Escherichia-driven enterotype. Bacterial diversity was significantly lower in all groups than in healthy controls, while the highest level of bacterial species richness was observed in cancer patients. Fifty-six bacterial species had abundance levels that differentiated diarrheal patient groups from the control group. Of these species, 52 and 4 (Bacteroides fragilis, Escherichia coli, Klebsiella pneumoniae, and Ruminococcus gnavus) were under-represented and over-represented, respectively, in all diarrheal patient groups. The relative abundances of propionate and butyrate were significantly lower in fecal samples from IBD and CDI patients than in control samples. Isobutyrate, propanate, and butyrate concentrations were lower in cancer, IBD, and CDI samples, respectively. Glycine and valine amino acids were over- represented in diarrheal patients. Conclusion Our data indicate that different external and internal factors drive comparable profiles of low diversity dysbiosis. While diarrheal-related low diversity dysbiosis may be a consequence of systemic cancer therapy, a similar phenotype is observed in cases of moderate to severe IBD, and in both cases, dysbiosis is exacerbated by incidence of CDI.